APLIKASI TEKNOLOGI PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS DALAM PEMANTAUAN POTENSI SUMBERDAYA PESISIR DAN LAUT DI KABUPATEN PANGKEP - Abdul Rauf; Kamil Yusuf; Asmidar Asmidar; Muh Kasnir; Mustamin Tajuddin (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2018)
Pangkep Regency has a large coastal area resource potential which is characterized by a long shoreline line of around 49.71 Km. Potential is spread along the coast which requires up-to-date information, namely position and area which is the basis for optimally and sustainably planning and managing coastal areas. The aim of this study is to map the potential of coastal ecosystem resources and coastal facilities along with their respective areas. This research uses a method with the Remote Sensing Technology and Geographic Information System (GIS) approach. The type of satellite data used is Spot-6 observation of 2018. The results obtained up-to-date data and information related to coastal area ecosystems and coastal facilities, namely mangrove ecosystems (327.22 ha), seagrass ecosystems (197.3 ha), coral reef ecosystems (0 Ha), artificial ecosystems in the form of ponds (13,792 , 57 ha) and beach facilities in the form of seven fishing ports and piers. This data is expected to be a material consideration for policy makers of the Pangkep Regency government in developing and developing their coastal areas in the future.